Responses of soil nematode abundance and food web to cover crops in a kiwifruit orchard - Li, Qing-mei; Qi, Xiao-Xu; Zhang, Hai-fang; Zhang, Yan-jun; Liu, Hong-mei; Zhao, Jian-ning; Yang, Dianlin; Wang, Hui (Frontiers in Plant Science, 2023)
Soil biodiversity plays an important role in both agricultural productivity and ecosystem functions. Cover crop species influence the primary productivity of the ecosystem and basal resources. However, it remains poorly understood how different cover crop treatments influence the community of soil nematodes in an orchard ecosystem. In this study, field experiments were conducted to investigate the effects of cover crop treatments with different species numbers, i.e., no cover crop (CK), two cover crop species (C2), four cover crop species (C4), and eight cover crop species (C8), on weed biomass, together with composition, abundance, and metabolic footprint of soil nematode community in a kiwifruit orchard. As compared to the CK group, the groups of cover crop treatments had lower weed biomass, which decreased with the increase of the cover crop diversity. Moreover, for the abundance of total nematodes, fungivores exhibited higher levels in C4 and C8 treatments than that in CK, bacterivores had a higher abundance in C4 treatment, and plant parasites had a higher abundance in C2 and C8 treatments. Cover crop treatments also changed the structure of nematode community and enhanced the nematode interactions and complexity of nematode community network. In addition, C4 increased the Wasilewska index but decreased the plant–parasite index. The metabolic footprints of fungivores were higher in cover crop treatments compared with CK, and C4 and C8 also increased the functional metabolic footprint of nematode. Soil nematode faunal analysis based on nematode metabolic footprints showed that C8 improved the soil nutrient status and food wed stability. Mantel test and redundancy analysis showed that soil microbial biomass nitrogen and carbon, organic carbon, nitrate nitrogen, moisture content, pH, and cover crop biomass were the main factors that affect soil nematode community. In conclusion, cover crop treatments with four or eight plant species displayed a positive role in weed control, improvement of soil health, and promotion of energy flow in the soil food web through the increase in the metabolic footprints of nematodes in kiwifruit orchard.